2009
DOI: 10.4047/jap.2009.1.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The change of rotational freedom following different insertion torques in three implant systems with implant driver

Abstract: STATEMENT OF PROBLEMImplant drivers are getting popular in clinical dentistry. Unlike to implant systems with external hex connection, implant drivers directly engage the implant/abutment interface. The deformation of the implant/abutment interface can be introduced while placing an implant with its implant driver in clinical situations.PURPOSEThis study evaluated the change of rotational freedom between an implant and its abutment after application of different insertion torques.MATERIAL AND METHODSThree kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 6 publications
5
16
0
6
Order By: Relevance
“…Rotational freedom of maximum 5 degrees is necessary for optimum stability between the hexagon of the prosthetic abutment and the implant. When rotational freedom exceeds 5 degrees, the torque needed to loosen the contact of implant‐prosthetic abutment is greatly reduced …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotational freedom of maximum 5 degrees is necessary for optimum stability between the hexagon of the prosthetic abutment and the implant. When rotational freedom exceeds 5 degrees, the torque needed to loosen the contact of implant‐prosthetic abutment is greatly reduced …”
Section: Discussionmentioning
confidence: 99%
“…When rotational freedom exceeds 5 degrees, the torque needed to loosen the contact of implant-prosthetic abutment is greatly reduced. [62][63][64] The rotational freedom between internal and external hexagon was examined in a pilot study in conjunction with the prosthetic abutment. The external hexagon presented greater rotational freedom (5.5 degrees) compared to the internal hexagon (2.9 degrees).…”
Section: Rotational Freedommentioning
confidence: 99%
“…The implant-abutment connection is most stable when the degree of rotational freedom is less than 2 , 66 and significant torque loss occurs when the degree is greater than 5 . [67][68][69][70] The anti-rotation design of the abutment can limit the rotational freedom, thereby maintaining well the stability of the joint. In the experiment of Yao et al, 71 all the abutments without anti-rotation design were rotated after cyclic loading, and fatigue fracture was observed.…”
Section: The Geometrical Morphology Materials Used and Manufacturimentioning
confidence: 99%
“…Over the past several decades, due to the reliable functional and aesthetic results, dental rehabilitation with implants has been widely accepted by dentists and patients. Conventionally, the implant/abutment interface is described as external or internal connection 2 . A review of existing literature has shown that amongst the cylindrical type of dental implants, the internal implant-abutment connections are greatly preferred.…”
Section: Introductionmentioning
confidence: 99%